The legal effects of EU agreements - Mendez, Mario (Oxford : Oxford University Press, 2012)
A comprehensive analysis of the legal effects of EU agreements explored in both comparative perspective and in terms of the ramifications for the legal orders of the member states. The book provides a thorough analysis of the case-law in this increasingly important area of EU law, valuable to academics and practitioners alike.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Apr. 5, 2013).
Keywords: Administrative law -- European Union countries